2017
DOI: 10.1080/10408398.2015.1130016
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acids and type 2 diabetes: Impact on the glycemic control mechanism

Abstract: There is a growing mortality related to co-morbidities associated with diabetes mellitus. Intake of polyunsaturated fatty acids (PUFA) has been associated with low cardiometabolic risk and reduction of inflammatory process. The objective of this paper is to review the impact of PUFA intake on glycemic control in diabetic patients as well as to elucidate the possible mechanisms involved. Medline/PubMed electronic database was searched to identify studies published within last five years regarding the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…These metabolic factors are well-established risks for ischemic heart disease [89] and were unaltered by ALA supplementation (Figure 1). This agrees with meta-analyses indicating no effects of n-3, n-6 or total PUFA intake on T2D risk or outcomes [4,90]; although, impacts in diabetes remain contentious [34,[90][91][92][93]. On the other hand, multiple trials show substitution of saturated fatty acids with PUFAs can lower blood glucose, HbA1c, and HOMA-IR in healthy adults [94].…”
Section: Systemic Phenotypesupporting
confidence: 81%
“…These metabolic factors are well-established risks for ischemic heart disease [89] and were unaltered by ALA supplementation (Figure 1). This agrees with meta-analyses indicating no effects of n-3, n-6 or total PUFA intake on T2D risk or outcomes [4,90]; although, impacts in diabetes remain contentious [34,[90][91][92][93]. On the other hand, multiple trials show substitution of saturated fatty acids with PUFAs can lower blood glucose, HbA1c, and HOMA-IR in healthy adults [94].…”
Section: Systemic Phenotypesupporting
confidence: 81%
“…It has been demonstrated that n-3 PUFA supplementation improved insulin sensitivity in Asian population of T2DM patients [ 30 ]. No benefits were found in Western populations [ 30 , 31 ]. This finding suggests that the favorable effect of n-3 PUFAs on insulin sensitivity may be affected by ethnicity [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…No benefits were found in Western populations [ 30 , 31 ]. This finding suggests that the favorable effect of n-3 PUFAs on insulin sensitivity may be affected by ethnicity [ 31 ]. On the other hand, Kusunoki et al found no significant association between HOMA-IR, which was used as a marker of glycemic control, and levels of EPA, DHA, and LA in serum phospholipids of Japanese patients with T2DM [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other studies have shown that circulating n-3 PUFA is inversely associated with insulin sensitivity in rodents (36) and type 2 diabetes (26,37). Several systematic reviews and meta-analyses focusing on dietary PUFAs and diabetogenic indicators have had inconsistent findings (38), including protective (39)(40)(41), harmful (41), and null findings (39,(41)(42)(43)(44)(45). Further studies are needed to explain these inconsistencies; one potential explanation is that dietary patterns (or combinations) of FAs may be protective against the diabetogenic state (46).…”
Section: Other Fas and Diabetogenic Indicatorsmentioning
confidence: 99%